2005
DOI: 10.2174/156720105774370258
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-based Self-Adjuvanting Vaccines

Abstract: Lipopeptides incorporating epitopes for CD4+ T cells and either CD8+ T cells or B cells have proven to be immunogenic in animal models and in humans and are well tolerated in these species. This form of vaccine candidate has great benefits over competing technology in terms of providing a totally synthetic and pure product that is effective when administered in the absence of any adjuvant, and is immunogenic when delivered by a variety of routes, including application to mucosal surfaces. The immune response c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 102 publications
1
37
0
Order By: Relevance
“…While Cop-1-induced neuroprotection could be obtained by passive T cell transfer, later studies demonstrated that more significant neuroprotection is achieved by subcutaneous injection of naked Cop-1 (without adjuvant) [17]. The T cell-mediated immune response elicited by this latter type of immunization is weak [46][47][48]. These results questioned the role of T cells in Cop-1-mediated neuroprotection, and led us to postulate additional mechanisms mediating Cop-1-induced neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…While Cop-1-induced neuroprotection could be obtained by passive T cell transfer, later studies demonstrated that more significant neuroprotection is achieved by subcutaneous injection of naked Cop-1 (without adjuvant) [17]. The T cell-mediated immune response elicited by this latter type of immunization is weak [46][47][48]. These results questioned the role of T cells in Cop-1-mediated neuroprotection, and led us to postulate additional mechanisms mediating Cop-1-induced neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for the immune-enhancing effect studied with other bacterial lipopeptides and lipoproteins suggests lipoprotein recognition of TLR receptors on cells of the innate immune system (20)(21)(22)(23). In this study, the interactions of rLP2086 with TLR2 and/or TLR2/TLR1 complexes on cell surfaces, and the subsequent cell activation, were confirmed using HEK293 hTLR2 cells that express human TLR2 and TLR1.…”
Section: Interactions Of Nmb Lipoproteins With Htlr2-expressing Cellsmentioning
confidence: 99%
“…This effect was enabled by induction of neutralizing antibodies (28,29) and by in vivo priming of epitope-specific cytotoxic T cells and memory T cells (30)(31)(32). Since antibodies to the lipid moieties are not generated in vivo, the immune-enhancing effect of the lipids is believed to be similar to that of a conventional adjuvant, and thus, bacterial lipoprotein/lipopeptidecontaining vaccines are recognized as one category of selfadjuvanting vaccines (21)(22)(23)33). Other categories include lipid-core peptides, single-chain palmitoylated peptides, and glycolipid analogues of bacterial lipopolysaccharides (21).…”
Section: Immune-enhancing Effects Of the N-terminal Lipids Of Rlp2086mentioning
confidence: 99%
See 2 more Smart Citations